“Smart” Triiodide Compounds: Does Halogen Bonding Influence Antimicrobial Activities? - Zehra Edis; Samir Haj Bloukh; Hamed Abu Sara; Hanusha Bhakhoa; Lydia Rhyman; Ponnadurai Ramasami (Pathogens, 2019)
Antimicrobial agents containing symmetrical triiodides complexes with halogen bonding may release free iodine molecules in a controlled manner. This happens due to interactions with the plasma membrane of microorganisms which lead to changes in the structure of the triiodide anion. To verify this hypothesis, the triiodide complex [Na(12-crown-4)2]I3 was prepared by an optimized one-pot synthesis and tested against 18 clinical isolates, 10 reference strains of pathogens and five antibiotics. The antimicrobial activities of this symmetrical triiodide complex were determined by zone of inhibition plate studies through disc- and agar-well-diffusion methods. The triiodide complex proved to be a broad spectrum microbicidal agent. The biological activities were related to the calculated partition coefficient (octanol/water). The microstructural analysis of SEM and EDS undermined the purity of the triiodide complex. The anionic structure consists of isolated, symmetrical triiodide anions [I-I-I]− with halogen bonding. Computational methods were used to calculate the energy required to release iodine from [I-I-I]− and [I-I···I]−. The halogen bonding in the triiodide ion reduces the antibacterial activities in comparison to the inhibitory actions of pure iodine but increases the long term stability of [Na(12-crown-4)2]I3.